How Have Divergent Global Emission Trends Influenced Long‐Range Transported Ozone to North America?. Issue 16 (23rd August 2022) - Mathur, Rohit; Kang, Daiwen; Napelenok, Sergey L.; Xing, Jia; Hogrefe, Christian; Sarwar, Golam; Itahashi, Syuichi; Henderson, Barron H.
Abstract: Several locations across the United States in noncompliance with the national standard for ground‐level ozone (O3 ) are thought to have sizable influences from distant extra‐regional emission sources or natural stratospheric O3, which complicate the design of local emission control measures. To quantify the amount of long‐range‐transported O3 (LRT O3 ), its origin, and change over time, we conduct and analyze detailed sensitivity calculations characterizing the response of O3 to emissions from different source regions across the Northern Hemisphere in conjunction with multidecadal simulations of tropospheric O3 distributions and changes. Model calculations show that the amount of O3 at any location attributable to sources outside North America varies both spatially and seasonally. On a seasonal‐mean basis, during 1990–2010, LRT O3 attributable to international sources steadily increased by 0.06–0.2 ppb yr −1 at locations across the United States and arose from superposition of unequal and contrasting trends in individual source‐region contributions, which help inform attribution of the trend evident in O3 measurements. Contributions of emissions from Europe steadily declined through 2010, while those from Asian emissions increased and remained dominant. Steadily rising NOx emissions from international shipping resulted in increasing contributions to LRT O3, comparable to those from Asian emissions in recent years. Central American emissions contribute a significant fraction of LRT O3 in southwestern United States. In addition to the LRT O3 attributable to emissions outside of North America, background O3 across the continental United States is composed of a sizable and spatially variable fraction that is of stratospheric origin (29%–78%). Plain Language Summary: Though implementation of control measures and technological advances have reduced ground‐level ozone pollution across the United States, increasing amounts of ozone pollution inter‐continentally transported from other world regions with increasing emissions, combined with changing and uncertain amounts of natural ozone from variability in stratosphere‐troposphere exchange processes, can confound design and implementation of local air pollution abatement strategies. "Background" or amount not produced locally constitutes a larger fraction of the ozone pollution at a location as local control measures are implemented. Detailed model calculations are analyzed to explain the role of the dominant source regions that drive the 1990–2010 changes noted in observed ground‐level ozone measurements across the United States. In recent years, the contributions of shipping emissions to ozone imported to the U.S. troposphere are comparable to those from the transport of ozone attributable to East Asian emissions and could be higher in the future if commercial shipping operations were to increase in response to anticipated growth in seaborne trade. In addition to the O3 attributable to emissions from different world regions, air masses entering the North American domain have sizable contributions of natural ozone of stratospheric origin, variability in which needs improved quantification to guide background ozone assessments and policy deliberations. Key Points: Changes in global emission patterns have and continue to alter long‐range transport and background O3 air pollution levels Long‐range‐transported O3 to North America has a prominent contribution from open sea shipping emissions and needs improved quantification Stratospheric O3 (ranging between 6 and 20 ppb) constitutes 29%–78% of the estimated Spring‐time background O3 across the continental United States